Sociolinguistic Study of Language Diversity in Classroom Learning Communication - Nova Kristian (Global Education Journal, 2026)
This research is motivated by the diverse use of language in learning communication in the classroom which shows that there is a variety of language variations between teachers and students. Differences in social backgrounds, language habits, and interaction situations in the classroom encourage the emergence of varied forms of language in the teaching and learning process. The purpose of this study is to identify the variety of languages used in learning communication, analyze the factors that influence language selection, and describe the forms of language variation that appear during the learning process. This study uses a qualitative approach by involving 15 students as informants through observation and interview techniques. Data analysis was carried out through data reduction, data presentation, and conclusion drawing based on the theory of language variation from William Labov (1972) and the ethnographic theory of communication from Dell Hymes (1974). The results of the study showed that a variety of formal languages were used in the delivery of materials and instructions, a semi-formal variety appeared in question and answer interactions, and a dominant non-formal variety in communication between students. The phenomenon of code switching and code mixing is also found in conversations in the classroom which are influenced by language habits and social closeness between students.